Sporadic Burkitt Lymphoma Presenting with Middle Cranial Fossa Masses with Sphenoid Bony Invasion and Acute Pancreatitis in a Child - Tal Dror; Virginia Donovan; Naomi Strubel; Sucharita Bhaumik (Case Reports in Oncological Medicine)
Acute pancreatitis in children is usually due to infection, trauma, or anatomical abnormalities and is rarely due to obstruction from malignancy. Sporadic Burkitt lymphoma (BL) is an aggressive non-Hodgkin B-cell lymphoma that usually involves the bowel or pelvis, with isolated cases presenting as acute pancreatitis. We report a case of BL in a 12-year-old male presenting as acute pancreatitis with obstructive jaundice and a right middle cranial fossa mass invading the sphenoid bone. The common bile duct in this case was dilated to 21 mm in diameter on abdominal ultrasound and to 26 mm on magnetic resonance cholangiopancreatography (MRCP), significantly greater than any value reported in the literature for BL. Given the rapidly progressing nature of BL, we emphasize the importance of recognizing heterogeneous presentations of this disease to improve patient survival. We also conclude that it is important to consider malignancy in a child with acute pancreatitis, particularly in the presence of obstructive jaundice or multisystem involvement. Other Presentations. This case report has no prior publications apart from the abstract being accepted to the 2020 SIOP (International Society of Pediatric Oncology) meeting and 2020 ASPHO conference (canceled due to the COVID-19 pandemic) and subsequently published as an abstract only in Pediatric Blood and Cancer. We have also presented the abstract as a poster presentation at our institution’s (NYU Langone Hospital—Long Island, previously known as NYU Winthrop) annual research day conference in 2020.